Role of neck circumference in measuring obesity in healthy adults - Sharma, Surabhi; Sharma, Kanav; Bajaj, Varun; Dudeja, Puja (Indian Journal of Community Health, 2019)
Background: Visceral fat or intra-abdominal fat is the adipose tissue surrounding mesenteries and omentum. This has been linked to lifestyle diseases like heart diseases, arthritis, stroke and even cancer. At present we have three tools to measure visceral fat area (VFA) – Bio impedance analysis, Magnetic resonance analyser and DEXA scan. Neck circumference measurement is a simple, easy to do and a quantifiable method of measuring visceral fat. Aim & Objective: This study aims to find correlation of visceral body fat with Neck Circumference (NC) and Body Mass Index. Methodology: A cross sectional study was carried out in a medical college of western Maharashtra, wherein 290 healthy males (>18 years) were selected by simple random sampling over a period of 7 months from (February 2018 – August 2018). Data was analyzed using SPSS version 20.0. Visceral body fat was measured using Body Space 720 and neck circumference using measuring tape. Results: We found a significant association between neck circumference and VFA. There is a strong association between NC of >35cm and VFA >100cm2. NC can be useful in field settings as it can be used easily by health care workers in predicting risk of lifestyle diseases.